2020
DOI: 10.18632/aging.103136
|View full text |Cite
|
Sign up to set email alerts
|

Long-noncoding RNA MALAT1 sponges microRNA-92a-3p to inhibit doxorubicin-induced cardiac senescence by targeting ATG4a

Abstract: The clinical application of doxorubicin (Dox) is limited due to its undesirable cardiotoxicity side effects. Cellular senescence plays an important role in Dox-induced cardiotoxicity. Exosomes derived from stem cells showed a therapeutic effect in Dox-induced cardiomyopathy (DIC). Hypoxia-preconditioned exosomes (exosome Hypoxia ) display pro-metabolism and pro-survival abilities. Several long-noncoding RNAs/microRNAs act as competing endogenous RNAs (ceRNAs) modulating DIC. No study investigated whether exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 70 publications
2
51
0
Order By: Relevance
“…Previous studies have shown that eliminate or reduce the cardiotoxicity of DOX and improve its curative effect is still an unsolved and prominent problem [29][30][31][32][33][34]. Furthermore, among six cardiomyocyte death forms (apoptosis, autophagy, necrosis, necroptosis, pyroptosis, and ferroptosis), accumulating evidences suggest an emerging role of pyroptosis in DOX-induced cardiomyopathy [5].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that eliminate or reduce the cardiotoxicity of DOX and improve its curative effect is still an unsolved and prominent problem [29][30][31][32][33][34]. Furthermore, among six cardiomyocyte death forms (apoptosis, autophagy, necrosis, necroptosis, pyroptosis, and ferroptosis), accumulating evidences suggest an emerging role of pyroptosis in DOX-induced cardiomyopathy [5].…”
Section: Discussionmentioning
confidence: 99%
“…As is mentioned above, exosomes generated from MSCs could inhibit DOX-induced cardiac senescence, this cardioprotective effect was mediated by overexpressing lncRNA MALAT1 in exosome Hypoxia . In detail, MALAT1 sponged microRNA-92a-3p, and the binding of them activated ATG4a , improving mitochondrial metabolism and thus partially playing a cardioprotective role in DOX-induced cardiac lesions 71 .…”
Section: Exosomes As Therapeutic Delivery Vehiclesmentioning
confidence: 98%
“…Moreover, hypoxia, used to be considered as a detrimental factor for it can induce ischemia-reperfusion (I/R) injury, has also intriguingly improved biological activity and showed better therapeutic functions. For instance, human adipose-derived mesenchymal stem cells (AT-MSCs) were treated with hypoxia and stimulated the secretion of exosome Hypoxia , exosome Hypoxia showed superiority in protecting cardiomyocytes from senescence induced by DOX 71 . The indistinguishably therapeutic effects of AT-MSC and BM-MSC implied that the secretion of exosomes was the common characteristic of MSCs, and the pretreatment of hypoxia could achieve better effects.…”
Section: Exosomes As Therapeutic Delivery Vehiclesmentioning
confidence: 99%
“…In addition, hypoxic MSCs-exos can improve myocardial cell metabolism disorders. Database and luciferase reporter assays show that hypoxia-induced ADMSCs-exo- MALAT1 can improve mitochondrial dysfunction in cardiomyocytes after Dox treatment by targeting MIR-92a-3p / ATG4A and combating cardiac aging ( 47 ). In addition, Zhuang et al found that the lncRNA NEAT1 was significantly enriched in exosomes derived from BMSCs treated with MIF.…”
Section: Cardiac Agingmentioning
confidence: 99%